2007
DOI: 10.1002/mrd.20716
|View full text |Cite
|
Sign up to set email alerts
|

p19Ink4d and p18Ink4c cyclin‐dependent kinase inhibitors in the male reproductive axis

Abstract: The loss of the cyclin-dependent kinase inhibitors (CKIs) p18(Ink4c) and p19(Ink4d) leads to male reproductive defects (Franklin et al., 1998. Genes Dev 12: 2899-2911; Zindy et al., 2000. Mol Cell Biol 20: 372-378; Zindy et al., 2001. Mol Cell Biol 21: 3244-3255). In order to assess whether these inhibitors directly or indirectly affect male germ cell differentiation, we examined the expression of p18(Ink4c) and p19(Ink4d) in spermatogenic and supporting cells in the testis and in pituitary gonadotropes. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…4A). Though the testes of p19 Ϫ/Ϫ male mice were slightly smaller than those of WT mice, p19-deficient males were fertile, which is in agreement with previous findings (27,28,40). After monitoring a cohort of 24 p19 Ϫ/Ϫ , 9 p19 ϩ/Ϫ , and 15 wild-type mice for 27 months, we found that 14 (58.3%) p19 Ϫ/Ϫ and 3 (30%) p19 ϩ/Ϫ mice spontaneously developed tumors, whereas only 2 (13.3%) WT mice displayed tumors at a similar age ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…4A). Though the testes of p19 Ϫ/Ϫ male mice were slightly smaller than those of WT mice, p19-deficient males were fertile, which is in agreement with previous findings (27,28,40). After monitoring a cohort of 24 p19 Ϫ/Ϫ , 9 p19 ϩ/Ϫ , and 15 wild-type mice for 27 months, we found that 14 (58.3%) p19 Ϫ/Ϫ and 3 (30%) p19 ϩ/Ϫ mice spontaneously developed tumors, whereas only 2 (13.3%) WT mice displayed tumors at a similar age ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…2C), supporting the activation of Cdk4 and/or Cdk6. These data are also consistent with the previous finding that p19 is predominantly expressed in the AL of pituitary (40). We then determined the kinase activity of Cdk4 and Cdk6 using GST-Rb as the substrate.…”
Section: Resultssupporting
confidence: 90%
“…One mg of testicular lysates from WT mice were prepared with 0.5% NP-40 lysis buffer as described previously [62]. Pre-cleared lysates were incubated overnight at 4°C with anti-GASZ, anti-MIWI, or no primary antibody, followed by incubation with protein G beads in 5% BSA to precipitate immune complexes.…”
Section: Methodsmentioning
confidence: 99%
“…An Nrf2 deficiency is associated with enhanced expression levels of genes involved in cell-cycle checkpoints' regulation, including the cyclin-dependent kinase inhibitor 2D (Cdkn2d, p19) and promyelocytic leukemia (PML). Cdkn2d inhibits Cdk4 leading to cell-cycle arrest at the G 1 /S transition (Buchold et al, 2007;Laine et al, 2007), whereas PML recruits Chk family kinases and p53 into the PML nuclear bodies, enhances the p53/Chk2 interaction (Louria-Hayon et al, 2003) and also orchestrates a nuclear tumor suppressor network that inactivate nuclear pAkt (Trotman et al, 2006). Cenp-F and Cenp-E have been implicated in spindle checkpoint regulation, kinetochore-microtubule capture and chromosome alignment and stability (Parra et al, 2002;Putkey et al, 2002).…”
mentioning
confidence: 99%